Effect of Microsilica Incorporation on The Fresh and Hardened Properties of Ordinary Portland Cement Concrete (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study investigated the effects of microsilica incorporation on the fresh and hardened properties of Ordinary Portland Cement Concrete (OPCC). Microsilica, a highly reactive pozzolanic material, was used to partially replace cement at 5%, 10%, and 15% by weight. The concrete samples were cured under normal conditions for seven days. The fresh properties were evaluated using the slump test, and hardened properties were determined through density, porosity, and rebound hardness tests. Results indicated that the addition of microsilica significantly reduced workability due to its high surface area but improved density and surface hardness up to 10% replacement. Porosity decreased consistently with increasing microsilica content, demonstrating enhanced compactness and reduced permeability. The study concludes that an optimal replacement level of 10% microsilica enhances both the mechanical and durability-related characteristics of OPCC.